Prospek kacang hijau pada musim kemarau di Jawa Tengah - Budhi Santoso Radjit; Nila P Sari (Buletin Palawija, 2012)
Mungbean (Vigna radiata) are resistant to drought and the price relatively high and stable compared than other legumes. In Demak district, mungbeans grown in the dry season after rice in heavy soil (Vertisol), without tillage, wihtout weeding and irrigation. The main problem on mungbean cultivation are drought and pest attacks.The intensity of pest attacks can be suppressed by pesticides. While drought can be avoided by planting 3–5 days after the rice harvested. Planting intimely way, the use of early maturity varieties and uniform maturity of pod (Vima 1) accompanied by an intensive pest control in the Tempuran and Megonten village Demak district can provide high yields, ranging from 1.72 to 1.92 t/ ha. The cost of production is needed between Rp 2.926.000 – Rp3.167.000/ha, can provide benefits ranging between Rp 7.669.000 million – Rp 8.594.000/ha and B/C ratio from 2.42 to 2.90. The application of introduction technology using Vima 1 variety that farmers do a positive impact on benefits which reached Rp 12.210.814,- (B/C ratio3,22), so its worth in the region has developed just as in the areas of agroecology Demak. The use of variety Vima 1 for 2 years after the technology display has covering 2000 ha in the Demak district, in order to accelerate the adoption of the technology it need to be disseminated effectively assembled this technology through the display of this technology insome areas that has the same condition. Local Government and relevant agencies should be involvedso that effective dissemination of technology.